First week of oil weathering of Colombian crude oil in the Colombian Caribbean Sea (2014)
Abstract: A module, MEUN (Módulo de Envejecimiento Universidad Nacional), that describes the processes that occur due to the interaction, also known as weathering, of the crude in an oil spill with the atmosphere and the ocean, was developed. This module, couples individual sub-models available in the literature used to describe the evaporation, emulsification, dispersion and spreading processes that characterize the first week after an ocean oil spill. MEUN predicts as well the variation in density and viscosity over time as a result of the weathering processes. All sub-model constants were adapted to the specific requirements of Colombian crudes, particularly to Cusiana (API 43.2) and Vasconia (API 20.7). While the first one represents light crudes, the second one is an example of heavier oils. These two crudes have high production and require marine transport. To evaluate MEUN predictions, experiments were carried out for evaporation and emulsification processes at conditions similar to those observed during an oil spill in the Colombian Caribbean Sea. In the case of the evaporation experiments, a wind tunnel of 3.0 m and a circular cross section of 30 cm in diameter was adapted to measure the weight loss of crude oil while varying the wind velocity between 3 m/s and 8 m/s. The emulsification process was simulated using the rotating-cylinder method, a standard in the weathering community. The emulsification experiments evaluated the effect of temperature (ranging from 22°C to 30°C) as well as the degree of evaporation of the crude oil in the rate and extent of emulsification. Variations in density and viscosity as a result of evaporation and emulsication were also measured. The evaporation results showed a strong dependence of evaporation rate with wind velocity, particularly for Cusiana. This behavior is not predicted by the state-of-the-art models used by the oil spill community. MEUN included a new correlation for the mass transfer coefficient that correctly predicts the evaporation process of Cusiana. Furthermore, the experiments revealed that Cusiana increases the pour point because of evaporation from 0°C for fresh oil up to 30°C when the evaporated fraction is 48%. When the oil temperature is below the pour point, something rather possible even at the relative high temperatures of the Colombian Caribbean Sea given the significant increase in pour point because of evaporation, the evaporation rate significantly decreases to virtually zero. This effect was included in MEUN. Vasconia presents the typical behavior for oil emulsification described in the literature as it forms an emulsion with a water content of 70-90% that becomes more stable as the evaporated fraction increases and the temperature decreases. Contrary, Cusiana only forms an emulsion when the temperature is below the pour point. The final version of MEUN reproduces these emulsification behaviors for Cusiana and Vasconia. When compared to well-established weathering software, such as ADIOS, MEUN gives predictions that are closer to the experimental behavior, particularly for Cusiana, as it considers the effect of pour point and predicts a combination of evaporation and dispersión considerably higher than that predicted by MEUN (100% vs 50% of the spilled amount, respectively, 30 hours after the spill).